Effects of artificial cycles with and without gonadotropin-releasing hormone agonist pretreatment on frozen embryo transfer outcomes in patients with adenomyosis - Muzi Li (Nature Portfolio, 2021)
Abstract Gonadotropin-releasing hormone agonist (GnRH-a) is generally added to the improve pregnancy outcomes of hormone replacement therapy cycles among patients with adenomyosis. We aimed to investigate whether adding GnRH-a can result in better pregnancy outcomes. This retrospective analysis included 341 patients with adenomyosis who underwent frozen embryo transfer (FET) after in vitro fertilization (IVF). The control group was treated only with hormone replacement therapy cycles to prepare the endometrium, and GnRH-a was added to the study group before hormone administration to adjust the menstruation cycle. Based on the similar baseline values and embryological data, there was no significant difference in the clinical pregnancy rates (40.63% vs. 42.54%, P = 0.72) and live birth rates (23.75% vs. 23.75%, P = 0.74) of the control and study groups. Other secondary outcomes, including the rates of clinical miscarriage, ectopic pregnancy, preterm birth and term birth, were not significantly different between the two groups. Compared with the hormone replacement therapy cycle alone, GnRH-a downregulation based on a hormone replacement therapy cycle may not increase the rate of clinical pregnancy or live birth of IVF-ET with FET among infertile patients with adenomyosis.